El potencial de manejo de especies maderables de rápido crecimiento en regeneración natural, sistemas agroforestales y plantaciones puras: Estudios de caso en Brasil, Perú y Costa Rica - Current, D.; Rossi, L.B.; Sabogal, C.; Nalvarte, W. (1998)
This article presents the preliminary results of case studies of three species with abundant regeneration in the natural regeneration of areas previously cleared for agriculture or pasture which have gained a place in timber markets (Guazuma crinita in Peru, Schizolobium amazonicum in Brazil and Cordia alliodora in Costa Rica). Due to the growing market interest in these species they are increasingly being integrated into the management of smallholdings in systems of management of natural regeneration, agroforestry systems and plantations. According to this preli minary research, the systems that have been preferred in the past by smallholders have been caring for natural regeneration and the establishment of agroforestry systems based on natural regeneration and plantings. The preference for these systems has been due to the low cost and ease of establishment and the ability to combine short-term benefits (crops and perennials) with timber production. Recently, due to incentives programs, more owners are opting for plantations whose greater costs are offset by incentives.